2021
DOI: 10.18203/2320-1770.ijrcog20211126
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting success of vaginal delivery in women with oligohydramnios undergoing induction of labour

Abstract: Background: Aim was to study the predicting factors for success of vaginal delivery, in women with oligohydramnios undergoing induction of labour.Methods: An observational study conducted in tertiary care centre Kamineni Hospital in 100 patients in 1-year duration with vaginal misoprostol tablets to predict the success of vaginal delivery in cases, if oligohydramnios undergoing induction of labor.Results: In our study total 100 cases was induced. Among these 81% had successful normal vaginal delivery and 19% h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…However, induction of labour leads to increase in risk of operative delivery and perinatal risks. 3 According to one study, the positive predictor of vaginal birth in patients undergoing induction of labour were to induce at term gestation with continuous electronic fetal monitoring in active labour 4 Pregnancies with idiopathic oligohydramnios, which account for over 50.7% of cases detected in the third trimester, are linked to a higher risk of low birth weight, meconium-stained liquor, caesarean delivery, and foetal distress. 5,6 In addition to a study reported a significant association between isolated oligohydramnios and long term neurological deficits of the offspring including developmental disorders, movement disorders, degenerative and demyelinization disorders.…”
Section: Original Articlementioning
confidence: 99%
“…However, induction of labour leads to increase in risk of operative delivery and perinatal risks. 3 According to one study, the positive predictor of vaginal birth in patients undergoing induction of labour were to induce at term gestation with continuous electronic fetal monitoring in active labour 4 Pregnancies with idiopathic oligohydramnios, which account for over 50.7% of cases detected in the third trimester, are linked to a higher risk of low birth weight, meconium-stained liquor, caesarean delivery, and foetal distress. 5,6 In addition to a study reported a significant association between isolated oligohydramnios and long term neurological deficits of the offspring including developmental disorders, movement disorders, degenerative and demyelinization disorders.…”
Section: Original Articlementioning
confidence: 99%